Thyroid Research - Leo, Simone; Vaidya, Bijay; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Thyroid Research is an online journal that aims to present the newest knowledge related to thyroid hormones, thyroid diseases and any related fields. The journal$1 (Bs regular readership includes researchers, clinicians and healthcare providers across the world. Thyroid Research encompasses a wide range of thyroidology topics including, diagnosis, pharmacological and other treatment methods, invasive treatment, physiological mechanisms of thyroid hormone action and regulation, immunological aspects, genetics, new guidelines in disease management, thyroid related diseases and complications.s
Keywords: Endocrinology; Cancer; Oncology; Endocrinology; Cancer Biology; Oncology